3D printing of olive pit powder-reinforced PVA/HAp scaffolds: a sustainable strategy for bone tissue engineering - Jagitay, Mohamed Bella; Ustundag, Gulpembe; Celik, Zehra Desen; Onur, Ayse; Bedir, Tuba; Torun, Sena Su; Ilhan, Elif; Gunduz, Oguzhan (SPRINGER, 2026)
The development of sustainable, biocompatible scaffolds for bone tissue engineering is crucial to address the limitations of conventional grafting approaches. In this study, we report the fabrication and characterization of 3D-printed scaffolds composed of polyvinyl alcohol (PVA), olive pith powder (OPP), and hydroxyapatite (HAp) using an extrusion-based technique. Four different formulations (1PVA/0OPP/HAp, 1PVA/1OPP/HAp, 2PVA/5OPP/HAp, and 5PVA/2OPP/HAp) were evaluated to investigate the effects of varying PVA-OPP ratios on the structural, mechanical, and biological properties of the scaffolds. FTIR analysis confirmed the successful incorporation of OPP and HAp into the PVA matrix through the retention of characteristic functional groups and enhanced hydrogen bonding. SEM analysis revealed that increasing OPP content improved inter-pore connectivity and surface roughness, with pore sizes ranging from similar to 382 to similar to 572 mu m, which is ideal for osteogenesis. Mechanical testing demonstrated a balance between stiffness and ductility depending on OPP concentration. The 1PVA/0OPP/HAp scaffold exhibited the highest tensile strength and modulus, while the 1PVA/1OPP/HAp group showed superior strain capacity. Cytocompatibility assessed by MTT assay and fluorescent staining showed that moderate OPP content (1PVA/1OPP/HAp and 5PVA/2OPP/HAp) promoted cell viability and spreading, while excessive OPP (2PVA/5OPP/HAp) impaired proliferation, possibly due to phenolic compound-induced oxidative stress. These results suggest that OPP can serve as a promising, sustainable filler in bone tissue engineering scaffolds when used at optimized concentrations.
Keywords: 3D printing; Olive pit powder; Polyvinyl alcohol; Hydroxyapatite; Bone tissue engineering; Sustainable biomaterials; POLYPHENOLS; BIOACTIVITY; Polymer Science